A Tale of Two Nations: Evaluating Terrorism and the Challenges of Counter Terrorism Strategies in Pakistan and Nigeria - Nte, Ngboawaji Daniel; Akaageregr, Isaac Ngutor; Khan, Irfan Ullah; Bienose, Onyeka (Law Research Review Quarterly, 2020)
The menace of terrorism the world over cannot be over emphasised as it remains the greatest existential threat facing mankind. All over the world, this nagging security quagmire has remained quite daunting. Consequently, countries around the world –advanced and developing have embarked on different shades of counter terrorism measures to stem this ugly scourge. In the light of the foregoing, this study is a modest evaluative and comparative study of a tale of two states-Pakistan and Nigeria in their quest to fight this ignoble menace. As countries with similar internal and external threats with significant challenges of governance and political stability, both countries have embarked on conscious counter terrorism measures ranging from socio-economic development programmes to de-radicalisation strategies. However, while the degrees of efficiency of counter terrorism measures varies between these two countries, the study shows that Pakistan appears to have made more concerted efforts than Nigeria, even though the threats are more magnified in Pakistan due to extensive international terrorist linkages in the country. What is more relevant here however is that both countries can learn from each other experiences while making the necessary adjustments to suit local realities bearing in mind that terrorism is more of a mind thing than mere tactical and operational form of militancy by non-state actors. In reaching the above proposition, the study relied on the content analysis of historical facts sourced from secondary sources but logically arranged to provide the required social science enterprise requirements while taking responsibility for any weakness therefrom.